In-situ formation of TiN during the hot-pressing of TiC–AlN ceramics. Issue 14 (15th July 2021) - Song, Bin; Yang, Wei; Babapoor, Aziz
Abstract: In this investigation, various amounts of AlN (0, 3.5, and 7 vol%) were added to TiC, and the resulted ceramics were studied in terms of microstructures and mechanical properties. The hot-pressing technique was employed as the sintering process at 2000 °C for 2 h under 35 MPa. Though a relative density of ~ 97% was obtained for the AlN free sample, the composite introduced by 7 vol% AlN reached its full density. The precipitation of carbon from the TiC matrix was proved by both X-ray diffractometry and microstructural observations. The deposited graphite contributed to removing the TiO2 surface impurity over sintering. Moreover, TiO2 reacted with AlN additive, generating in-situ TiN. Such a phase mainly dissolved into the AlN phase, leading to the formation of (Al, Ti)N solid solution. The highest Vickers hardness of 2745 HV0.5kg was attained for the monolithic ceramic, thanks to the lack of AlN as a softer phase. Finally, incorporating 7 vol% AlN increased the flexural strength of TiC by almost 33% as a result of porosity removal and fine-grain, standing at 790 MPa.